2021
DOI: 10.36681/tused.2021.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7E ınstructional strategy on the achievement and retention of students in bıology in public secondary schools in Adamawa State, Nigeria

Abstract: The abstract should be in Palatino Linotype as the font type, 9 pt., between 150-250 words.  The aim of this study was to investigate the effect of the 7E instructional strategy on the achievement and retention of SS II (11th grade) Biology students in public secondary schools in Nigeria. Intact classes of 60 students were randomly selected and denoted as the experimental group, which was taught with the 7E instructional strategy, and the control group, which was taught using the traditional, teacher-centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Studies focusing on understanding of diffusion and osmosis confirmed that students show a considerable number of misconceptions and difficulties that are resistant to change by traditional teaching methods (Abdullahi, et al, 2021;Ekon & Edem, 2018;Obochi, 2021). Ekon & Edem (2018) pointed many misconceptions about concentration and tonicity and the influence of life forces on diffusion and osmosis among biology students.…”
Section: Misconception In Diffusion and Osmosismentioning
confidence: 99%
“…Studies focusing on understanding of diffusion and osmosis confirmed that students show a considerable number of misconceptions and difficulties that are resistant to change by traditional teaching methods (Abdullahi, et al, 2021;Ekon & Edem, 2018;Obochi, 2021). Ekon & Edem (2018) pointed many misconceptions about concentration and tonicity and the influence of life forces on diffusion and osmosis among biology students.…”
Section: Misconception In Diffusion and Osmosismentioning
confidence: 99%
“…These stages are: elicit, engage, explore, explain, elaborate, evaluate, and extend (Eisenkraft, 2003). The learning cycle emphasized that learning should start with (1) eliciting the prior knowledge of the learners; (2) engaging the learners by using a discrepant event to arouse their interest; (3) exploring the skills and knowledge of the students; (4) explaining the new concepts by allowing students to verbalize and clarify the concept; (5) elaborating the newly learned concepts of the students through questioning; (6) evaluating the learning outcome of the students through the use of formative assessment; and (7) extending the knowledge by helping students to connect the concept to different contexts; or transfer the knowledge to other contexts (Abdullahi et al, 2021;Eisenkraft, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on the effectiveness of constructivist teaching approaches on students' learning. The studies about the instructions based on the learning cycle model showed that learning cycle approaches help students improve academic achievement (Khan et al, 2020); self-efficacy (Puspita & Fardillah, 2021); critical thinking skills (Marfilinda et al, 2020;Tecson et al, 2021); retention (Abdullahi et al, 2021;Wodaj & Belay, 2021); science process skills (Khairani et al, 2021;Komikesari et al, 2020;Silitonga et al, 2021) and attitudes toward science (Abdullahi et al, 2021;Ören & Tezcan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, students still have difficulty learning the concept of system material in the human body, because it is considered broad and abstract [3]. Students need to study and understand the body's biological system because it teaches students to appreciate the subject ICMScE and see how it works or processes in real life [4]. Biology learning also emphasizes student interactions and experiences in understanding everything that happens in life [5].…”
Section: Introductionmentioning
confidence: 99%